Target‐Induced and Equipment‐Free DNA Amplification with a Simple Paper Device. (8th January 2016) - Liu, Meng; Hui, Christy Y.; Zhang, Qiang; Gu, Jimmy; Kannan, Balamurali; Jahanshahi‐Anbuhi, Sana; Filipe, Carlos D. M.; Brennan, John D.; Li, Yingfu
Abstract: We report on a paper device capable of carrying out target‐induced rolling circle amplification (RCA) to produce massive DNA amplicons that can be easily visualized. Interestingly, we observed that RCA was more proficient on paper than in solution, which we attribute to a significantly higher localized concentration of immobilized DNA. Furthermore, we have successfully engineered a fully functional paper device for sensitive DNA or microRNA detection via printing of all RCA‐enabling molecules within a polymeric sugar film formed from pullulan, which was integrated with the paper device. This encapsulation not only stabilizes the entrapped reagents at room temperature but also enables colorimetric bioassays with minimal steps.